2005
DOI: 10.1509/jmkg.69.3.80.66360
|View full text |Cite
|
Sign up to set email alerts
|

Do Suppliers Benefit from Collaborative Relationships with Large Retailers? An Empirical Investigation of Efficient Consumer Response Adoption

Abstract: Collaborative manufacturer-retailer relationships based on efficient consumer response (ECR) have become ubiquitous over the past decade. Yet academic studies of ECR adoption and its impact on marketing relationships are relatively scarce. Inspired by the relational view of competitive advantage, the authors empirically investigate whether the extent to which suppliers of a major retailer adopt ECR has a beneficial impact on their outcomes. The results demonstrate that whereas ECR adoption has a positive impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
265
2
12

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 360 publications
(286 citation statements)
references
References 59 publications
(82 reference statements)
7
265
2
12
Order By: Relevance
“…(Erin Anderson and Weitz, 1992) showed that 17 perceptual differences can negatively affect the relationships among chain members and 18 results dissatisfaction and conflict. Similarly, while buyers and suppliers both benefited from 19 collaborations, suppliers had a greater feeling of inequality (Corsten and Kumar (2005).…”
mentioning
confidence: 99%
“…(Erin Anderson and Weitz, 1992) showed that 17 perceptual differences can negatively affect the relationships among chain members and 18 results dissatisfaction and conflict. Similarly, while buyers and suppliers both benefited from 19 collaborations, suppliers had a greater feeling of inequality (Corsten and Kumar (2005).…”
mentioning
confidence: 99%
“…It is clear that collaboration is the key to achieve supply chain management. Increasingly, firms are building collaborative relationships with their supply chain partners in order to achieve efficiencies, flexibility, and a competitive advantage (Nyaga et al, 2010) by adopting a long-term approach with joint efforts by each partner create unique value that neither partner can create independently (Corsten and Kumar, 2005). Collaboration is vital for firms in supply chain (Su et al, 2008) because of the fact that the ability to compete has been directly linked with their ability to collaborate with other enterprises.…”
Section: Asian Economic and Financial Reviewmentioning
confidence: 99%
“…The ECR foundation is that all stakeholders in a retail value-chain should be understood as a single entity, working together to maximize chain efficiency and add value to the end customer (Reyes & Bhutta, 2005). The ECR philosophy comprises four main areas (Corsten & Kumar, 2005): demand management, supply management; enablers (e.g. standards of electronic messages); and interfaces or integrating elements (e.g.…”
Section: Concept Of Category Managementmentioning
confidence: 99%